PO.1.12 Transcriptome profiling and autoimmunity-related serological markers identify TP53 and C3aR as drug targets in neuropsychiatric systemic lupus erythematosus. (27th September 2022) - Lindblom, J; Toro-Domínguez, D; Carnero-Montoro, E; Borghi, MO; Castillo, J; Iacobaeus, E; Enman, Y; Repsilber, D; Mohan, C; Alarcón-Riquelme, M; Barturen, G; Parodis, I
Abstract : Purpose: Involvement of the nervous system is a common but poorly understood manifestation of systemic lupus erythematosus (SLE), termed neuropsychiatric SLE (NPSLE). Although studies have reported varying prevalence estimates, NPSLE affects at least 20% of patients with SLE within the first years of the disease course. The management of NPSLE is poorly optimised and specific treatment is lacking. The aim of this study was to investigate expression quantitative trait loci (eQTLs), the transcriptome, and autoimmunity-related cytokines and autoantibodies in patients with central nervous system (CNS) lupus to gain insights into underlying genetics and biologic mechanisms towards identification of novel drug targets. Methods: We analysed differentially expressed genes (DEGs), pathways and their druggability via the Drug Gene Interaction database (DGIdb) in active CNS lupus (n=26) versus healthy controls (HC; n=497), and eQTLs in active or past CNS lupus (n=53), based on validated (identified in two independent SLE populations) DEGs in SLE (n=350) versus HC (n=497), in whole blood collected within the frame of the European PRECISESADS consortium. CNS lupus was defined according to SLE Disease Activity Index 2000 (SLEDAI-2K) CNS items or by CNS manifestations such as chorea, acute confusional state, transverse myelitis, and aseptic meningitis in the absence of predisposing conditions unrelated to SLE. Genome-wide RNA-sequencing and genotyping was previously performed by Illumina assays, and serum levels of 17 cytokines were analysed using a Luminex assay and ELISA (Barturen et al. 2021). Results: Among 5631 significant and validated DEGs in active CNS patients compared with HC, 1922 unique DEGs were tagged to 21 and 176 significant KEGG and Reactome pathways, respectively. Pathways included 'Interferon signalling', 'TNF signalling' and 'Toll-like Receptor Cascades'. The pathways included 29 of 59 DEGs with a fold change (FC) <0.66 or >1.5, 6 genes from 14 significant cis-eQTLs and 10 genes from 22 trans-eQTLs, and 2 genes from 8 cytokines that differed significantly between active CNS lupus and HC. These genes could be targeted by 496 different drugs, with the Bruton tyrosine kinase (BTK) inhibitor ibrutinib and the anti-CD20 B cell depleting monoclonal rituximab with ability to interfere with tumour protein P53 (TP53) activity, and a complement C3a Receptor (C3aR) antagonist being of particular interest. Conclusions: Integrated multilevel omics analysis revealed a set of enriched pathways of potential interest for future drug investigation in CNS lupus, including BTK and C3aR inhibition, and B cell depletion.